Beyond shanties and rubbles a study on the coverage of demolitions by two national dailies - Belisario, Paul Joseph Corpuz 1988- (2012)
"Squatting is a manifestation of deep social problems (Murphy, 1993), such as government's failure to provide effective housing programs for the poor (McAuslan, 1985), lack of economic opportunities in rural areas (Murphy, 1993), and expensivehousingcosts for the people (Panganiban &Urrutia, 1981). However, such aspects of the plight of informal settlers in the Philippines are not properly addressed by the government. Likewise, media outlets give minimal exposure to these issues. The struggles of the urban poor are usually translated in demolition stories, which normally highlight people's resistance and violence. In calling for the implementation of better government programs for the poor, the participation of other members of the society, specifically the middle class, is highly important (Murphy, 1993). Thus, the media plays an important role in exposing the plight of the marginalized (in this case, that of the informal settler) and engaging those from the upper class in the policy-making process, as media emphasis on a particular issue tells people "what to think about" (Dearing and Rogers, 1996). This study explores the presentation of the plight of the urban poor through the demolition coverage by The Philippine Star and Philippine Daily Inquirer, twomajor newspaper with the highest readership in the Philippines. The researchers analyzed demolition stories published by the two dailies from September 23, 2010 to September 23, 2011. First, the manifest (emphasis) content was measured by evaluating the articles' placement (page, horizontal and vertical fold), headline size, cut area size, and presence of photographs. The latent (tendency and focus) content was then determined through the recurrent themes discussed in the stories. The results of the content analysis were then validated by the data obtained from the focus interviews with news gatherers (reporters and processors (editors). The researchers discovered that the Philippine Daily Inquirer gave more importance to demolitions than did its rival, The Philippine Star. The former published 29 demolition stories within one year while the latter only printed 19 articles. It can be said the The Philippine Daily had a better coverage of demolitions than The Philippine Star, as it scored higher in utilizing different physical dimensions of an article to catch the readers' attention. However, it is also important to note that there are no significant differences between the Philippine Daily Inquirer and The Philippine Star in terms of placement, use of headline and cut area sizes, and presenting photographs. Moreover, both national dailies did not threat the demolitions in Metro Manila of national importance. All demolition stories fall under the Metro News Section. The articles from the Philippine Daily Inquirer highlighted the 1) obstruction of informal settlement to government and private infrastructure development, 2) plans for resettlement by the government, 3) provocation of violence by the settlers and 4) unsettled legal issues between the settlers and the authorities. The Philippine Star gave more emphasis to 1) plans for settlement by the government and 2) location of settlements in a danger zone. It can be concluded that the coverage of demolitions by the Philippine Daily Inquirer and The Philippine Star is not sufficient in helping a bigger portion of the population understand the plight of the urban poor. Deeper analysis of demolition issues, such as violation of the human rights and lack of due process, are not exposed and discussed in the reports. Violence is emphasized more than the reason behind such resistance from the residents. Since no follow-up reports are made, the struggles of the people in a particular urban poor community are easily forgotten. The information surrounding demolitions has been filtered and carefully selected by the news gatherers based on the news values that they deem most fit for publication. While news gatherers say they highlight human interest in their stories, it is not that evident in the reports. A better framing of the issue of informal settlers has to be devised to better present the concerns of the urban population and engage a bigger portion of them in participating in the advancement of the interests of the marginalized."